Structural perspectives on antimicrobial chemokines - Nguyen, Leonard T.; Vogel, Hans (Frontiers in Immunology, 2012)
Chemokines are best known as signaling proteins in the immune system. Recently however, a large number of human chemokines have been shown to exert direct antimicrobial activity. This moonlighting activity appears to be related to the net high positive charge of these immune signaling proteins. Chemokines can be divided into distinct structural elements and some of these have been studied as isolated peptide fragments that can have their own antimicrobial activity. Such peptides often encompass the α-helical region found at the C-terminal end of the parent chemokines, which, similar to other antimicrobial peptides, adopt a well-defined membrane-bound amphipathic structure. Because of their relatively small size, intact chemokines can be studied effectively by NMR spectroscopy to examine their structures in solution. In addition, NMR relaxation experiments of intact chemokines can provide detailed information about the intrinsic dynamic behavior; such analyses have helped for example to understand the activity of TC-1, an antimicrobial variant of CXL7/NAP-2. With chemokine dimerization and oligomerization influencing their functional properties, the use of NMR diffusion experiments can provide information about monomer-dimer equilibria in solution. Furthermore, NMR chemical shift perturbation experiments can be used to map out the interface between self-associating subunits. Moreover, the unusual case of XCL1/lymphotactin presents a chemokine that can interconvert between two distinct folds in solution, both of which have been elucidated. Finally, recent advances have allowed for the determination of the structures of chemokines in complex with glycosaminoglycans, a process that could interfere with their antimicrobial activity. Taken together, these studies highlight several different structural facets that contribute to the way in which chemokines exert their direct microbicidal actions.